Prostaglandin E2 facilitates neurite outgrowth in a motor neuron-like cell line, NSC-34 - Hiroshi Nango; Yasuhiro Kosuge; Hiroko Miyagishi; Kosuke Sugawa; Yoshihisa Ito; Kumiko Ishige (Elsevier, 2017)
Prostaglandin E2 (PGE2) exerts various biological effects by binding to E-prostanoid receptors (EP1-4). Although recent studies have shown that PGE2 induces cell differentiation in some neuronal cells such as mouse DRG neurons and sensory neuron-like ND7/23 cells, it is unclear whether PGE2 plays a role in differentiation of motor neurons. In the present study, we investigated the mechanism of PGE2-induced differentiation of motor neurons using NSC-34, a mouse motor neuron-like cell line. Exposure of undifferentiated NSC-34 cells to PGE2 and butaprost, an EP2-selective agonist, resulted in a reduction of MTT reduction activity without increase the number of propidium iodide-positive cells and in an increase in the number of neurite-bearing cells. Sulprostone, an EP1/3 agonist, also significantly lowered MTT reduction activity by 20%; however, no increase in the number of neurite-bearing cells was observed within the concentration range tested. PGE2-induced neurite outgrowth was attenuated significantly in the presence of PF-0441848, an EP2-selective antagonist. Treatment of these cells with dibutyryl-cAMP increased the number of neurite-bearing cells with no effect on cell proliferation. These results suggest that PGE2 promotes neurite outgrowth and suppresses cell proliferation by activating the EP2 subtype, and that the cAMP-signaling pathway is involved in PGE2-induced differentiation of NSC-34 cells. Keywords: Prostaglandin E2, E-prostanoid receptors, Motor neuron, Neurite outgrowth, cAMP